DDPH, a novel antihypertensive agent, is a potential dual inhibitor of hepatic CYP2D and CYP3A. (5th March 2016) - Zhu, Yinsong; Hu, Jiong; He, Wenjuan; Gao, Xiujuan; Ren, Ping; Chen, Hui
Abstract: DDPH (1-(2, 6-dimethylphenoxy)-2-(3, 4-dimethoxyphenylethylamino) propane hydrochloride) is a promising novel antihypertensive agent, with potent antihypertensive, neuroprotective and cardioprotective effects. This study aimed to investigate the effects of DDPH on the expression and activity of hepatic cytochrome P450 (CYP) isoforms and evaluate the metabolic drug–drug interactions of DDPH with propafenone. Our results showed that orally administered DDPH (12.5–50 mg/kg/d) for 7 days significantly inhibited CYP2D1 and CYP3A1 activity and mRNA and protein expression but weakly increased CYP1A2 activity and expression in rats. Enzyme kinetics studies showed that DDPH was a competitive inhibitor of CYP2D1 and mixed inhibitor of CYP3A1 in rat liver microsomes with Ki values of 3.70 ± 0.42 μM and 4.79 ± 1.10 μM respectively. With human liver microsomes, DDPH was a noncompetitive inhibitor of CYP2D6 (Ki  = 0.85 ± 0.06 μM) and mixed inhibitor of CYP3A (Ki  = 2.15 ± 0.41 μM). Further in vivo study showed that oral administration of DDPH (12.5–50 mg/kg/d) for 7 days in rats significantly increased the area under the plasma concentration–time curve (AUC) of propafenone by 25.4%–63.9%, with a concomitant decrease in the plasma clearance. In conclusion, the results indicated that DDPH inhibited CYP2D and CYP3A activities and down-regulated their protein expression and mRNA transcription. DDPH might cause metabolic drug–drug interactions through modulation of the activity and expression of CYP2D and CYP3A. This information could be important in the prediction of possible drug–drug interactions as well as for the effective therapy and the limitation of toxicity of DDPH in clinical practice. Highlights: DDPH inhibits CYP2D1 and CYP3A1 activity, mRNA and protein expression in rats. DDPH is a potential dual inhibitor of hepatic CYP2D and CYP3A in rats and humans. DDPH affects the pharmacokinetics of propafenone, leading to an increase of AUC. Caution is required when DDPH is co-administered with CYP2D or CYP3A substrates.